Effectiveness of flipped classroom model in improving students’ learning - Apdul Ajis Hasibuan; Ponidi Ponidi (Inovasi Kurikulum, 2025)
The learning process faces many challenges in its implementation, including low student participation and a lack of independent learning. Many students tend to be passive and rely solely on teacher explanations, resulting in a relatively low understanding of the material. This condition requires innovative learning strategies that can activate students' roles. This study aims to evaluate the effectiveness of the flipped classroom learning model in increasing the participation of eighth-grade students at MTs Al-Wasliyah Tembung in Social Studies. The study employed a qualitative descriptive approach, utilizing a case study method, with data collected through observation, interviews, and documentation. The results showed that the implementation of the flipped classroom significantly improved students' learning readiness, as evidenced by the increasing number of students actively participating in class discussions. Additionally, this model had a positive impact on learning motivation, self-confidence, and the ability to collaborate in groups. Thus, the study concluded that the flipped classroom model can be an effective alternative learning strategy to improve the quality of Social Studies teaching and learning in Islamic Junior High Schools (Madrasah Tsanawiyah).   Abstrak Pembelajaran di Madrasah Tsanawiyah masih menghadapi tantangan berupa rendahnya partisipasi peserta didik dan kurangnya kemandirian belajar. Banyak peserta didik cenderung pasif serta hanya bergantung pada penjelasan guru, sehingga pemahaman materi yang diperoleh relatif rendah. Kondisi ini menuntut adanya inovasi strategi pembelajaran yang mampu mengaktifkan peran peserta didik. Penelitian ini bertujuan mengevaluasi efektivitas model pembelajaran kelas terbalik (flipped classroom) dalam meningkatkan partisipasi peserta didik kelas VIII MTs Al-Wasliyah Tembung pada mata pelajaran Ilmu Pengetahuan Sosial. Penelitian dilaksanakan dengan pendekatan deskriptif kualitatif menggunakan metode studi kasus, dengan data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa penerapan flipped classroom mampu meningkatkan kesiapan belajar peserta didik secara signifikan, terlihat dari semakin banyaknya peserta didik yang aktif terlibat dalam diskusi kelas. Selain itu, model ini juga berpengaruh positif terhadap motivasi belajar, rasa percaya diri, serta kemampuan kolaborasi dalam kelompok. Dengan demikian, penelitian menyimpulkan bahwa model flipped classroom dapat menjadi alternatif strategi pembelajaran yang efektif untuk meningkatkan kualitas proses belajar mengajar IPS di Madrasah Tsanawiyah. Kata Kunci: aktivitas belajar; efektivitas belajar; model kelas terbalik